Prevention of hooligan behavior at football stadiums - Kowalska, Jolanta Elżbieta (Journal of Education, Health and Sport, 2019)
This study attempts to present the problem of hooligan behavior at football stadiums in the context of the Council of Europe guidelines, preventive measures (including project method experience).